St. Gallen, eine Reformationsstadt ohne Druckerei - Gamper, Rudolf (Zwingliana, 2018)
It was the city of St. Gall which introduced reformation as one of the first cities of the Swiss confederation. Though the conditions were favourable to the operation of a printing office, no printer decided to settle in the town. The paper discusses the reasons and the consequences which the lack of a printing office entailed.